Sex-specific distributions and determinants of thoracic aortic diameters in the elderly. Issue 2 (24th September 2019) - Bons, Lidia R; Rueda-Ochoa, Oscar L; El Ghoul, Khalid; Rohde, Sofie; Budde, Ricardo PJ; Leening, Maarten JG; Vernooij, Meike W; Franco, Oscar H; van der Lugt, Aad; Roos-Hesselink, Jolien W; Kavousi, Maryam; Bos, Daniel
Abstract : Objective: To provide population-based distributions of thoracic aortic diameters in men and women aged 55 years or older and to identify determinants of thoracic aortic diameters. Methods: From 2003 to 2006, 2505 participants (1208 men, mean age 69.1±6.8 years) from the prospective population-based Rotterdam Study underwent non-enhanced cardiac CT. The diameter of the ascending (AA) and descending aorta (DA) was measured at the level of the pulmonary bifurcation. Results: The mean diameter of the ascending and descending aorta was substantially larger in men (38±4 mm and 30±2 mm) than in women (35±3 mm and 27±2 mm). An ascending aortic diameter of larger than 40 mm was found in 228 (18.9%) men and 76 (5.9%) women and a descending aortic diameter larger than 40 mm was found in two men and no women. Male sex was found to be independently associated with larger DA diameter (standardised β 0.24, 95% CI 0.19 to 0.30), while a statistically non-significant trend was found for the AA diameter (standardised β 0.06, 95% CI 0.00 to 0.12). Age, height, weight and traditional cardiovascular risk factors were also associated with larger AA and/or DA diameters. Diabetes was associated with smaller AA and DA diameters. We found no evidence for effect modification by sex. Conclusions: In persons aged 55 years or older, an ascending aortic diameter of 40 mm or larger was found in 18.9% of men and 5.9% of women. Given the importance of sex, sex-specific distribution values may prove useful in clinical practice, even when correcting for body surface area or height.